Condensate Density of a Bose Gas Confined between Two Parallel Plates in Canonical Ensemble within Improved Hartree-Fock Approximation - Thu, Nguyen Van (VNU Journal of Science: Mathematics - Physics; Vol 36 No 4, 2020)
By means of Cornwall-Jackiw-Tomboulis (CJT) effective action approach, the condensate density of a dilute Bose gas is investigated in the canonical ensemble. Our results show that the condensate density is proportional to a half-integer power law of the s -wave scattering length and distance between two plates. Apart from that, these quantities also depend on the particle number and area of each plate.